2023
DOI: 10.1093/plphys/kiad048
|View full text |Cite
|
Sign up to set email alerts
|

Elicitor-induced plant immunity relies on amino acids accumulation to delay the onset of bacterial virulence

Abstract: Plant immunity relies on the perception of Microbe-Associate Molecular Patterns (MAMPs) from invading microbes to induce defense responses that suppress attempted infections. It has been proposed that MAMP-triggered immunity (MTI) suppresses bacterial infections by suppressing the onset of bacterial virulence. However, the mechanisms by which plants exert this action are poorly understood. Here, we showed that MAMP perception in Arabidopsis (Arabidopsis thaliana) induces the accumulation of free amino acids in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…Several amino acids and sugars produced significant growth over 60 hours of incubation ( Fig 1B ). Of special interest were plant metabolites previously shown to have an impact on Pst DC3000 infections [ 4 , 12 , 13 , 26 ]. GABA, a highly abundant amino acid in the LA of tomato plants, produced robust growth, as did L-glutamine, sucrose, and D-glucose ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several amino acids and sugars produced significant growth over 60 hours of incubation ( Fig 1B ). Of special interest were plant metabolites previously shown to have an impact on Pst DC3000 infections [ 4 , 12 , 13 , 26 ]. GABA, a highly abundant amino acid in the LA of tomato plants, produced robust growth, as did L-glutamine, sucrose, and D-glucose ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
“…PRRs can be activated with purified synthetic MAMPs to elicit plant immunity prior to bacterial infection. Such activation of plant immunity elicits changes in the metabolite composition of the LA [ 12 ], which in turn, suppress the expression of Pst DC3000 T3SS and coronatine biosynthesis genes, thus compromising Pst DC3000 virulence and infectivity [ 12 14 ]. Altogether, these studies demonstrate that plant defense responses drive changes in the composition of LA metabolites that inhibit Pst DC3000 growth and prevent the onset of plant disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, a caveat to this conclusion is that the single time point in our metabolomics analysis likely does not capture the full spectrum of PAMP-induced changes that occur. In this regard, a recent study reported that nine different amino acids significantly accumulated within the apoplast of Arabidopsis leaves 24 hours after flg22 treatment 53 . Because high concentrations of amino acids can repress T3SS genes in P. syringae , the authors concluded that increased amino acid levels within the apoplast contributes to flg22-induced T3SS repression and PTI 53 .…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, a recent study reported that nine different amino acids significantly accumulated within the apoplast of Arabidopsis leaves 24 hours after flg22 treatment 53 . Because high concentrations of amino acids can repress T3SS genes in P. syringae , the authors concluded that increased amino acid levels within the apoplast contributes to flg22-induced T3SS repression and PTI 53 . However, these late-occurring changes are unlikely to be causal for T3SS repressive environment that is established within ten hours after PAMP perception ( Fig.…”
Section: Discussionmentioning
confidence: 98%